At the Interface of Life and Death: Post-mortem and Other Applications of Vaginal, Skin, and Salivary Microbiome Analysis in Forensics - Ahannach, Sarah; Spacova, Irina; Decorte, Ronny; Jehaes, Els; Lebeer, Sarah (Frontiers in Microbiology, 2021)
Microbial forensics represents a promising tool to strengthen traditional forensic investigative methods and fill related knowledge gaps. Large-scale microbiome studies indicate that microbial fingerprinting can assist forensics in areas such as trace evidence, source tracking, geolocation and circumstances of death. Nevertheless, the majority of forensic microbiome studies focus on soil and internal organ samples, while the microbiome of skin, mouth and especially vaginal samples that are routinely collected in sexual assault and femicide cases, remain underexplored. This review discusses the current and emerging insights into vaginal, skin and salivary microbiome-modulating factors during life (e.g., lifestyle, health status) and after death (e.g., environmental influences, post-mortem interval) based on next-generation sequencing. We specifically highlight the key aspects of female reproductive tract, skin and mouth microbiome samples relevant in forensics. To fill the current knowledge gaps, future research should focus on the degree to which the post-mortem succession rate and profiles of vaginal, skin and saliva microbiota are sensitive to abiotic and biotic factors, presence or absence of oxygen and other gases as well as the nutrient-richness of the environment. Application of this microbiome-related knowledge could provide valuable complementary data to strengthen forensic cases, for example to shed light on the circumstances surrounding death with (post-mortem) microbial fingerprinting. Overall, this review synthesizes the present knowledge and aims to provide a framework to adequately comprehend the hurdles and potential application of vaginal, skin and salivary post-mortem microbiomes in forensic investigations.